2007
DOI: 10.1152/ajpheart.01078.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cold-induced cutaneous vasoconstriction is mediated by Rho kinase in vivo in human skin

Abstract: Thompson-Torgerson CS, Holowatz LA, Flavahan NA, Kenney WL. Cold-induced cutaneous vasoconstriction is mediated by Rho kinase in vivo in human skin. Am J Physiol Heart Circ Physiol 292: H1700-H1705, 2007. First published December 15, 2006; doi:10.1152/ajpheart.01078.2006 is the initial thermoregulatory response to cold exposure and can be elicited through either whole body or localized skin cooling. However, the mechanisms governing local cold-induced VC are not well understood. We tested the hypothesis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
108
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 44 publications
7
108
0
Order By: Relevance
“…In vitro data suggest that ROS can induce vasoconstriction through Rho kinase-dependent mechanisms (3). Rho kinase has been shown to have an increasingly important role in cold-induced vasoconstriction (29) and connects well with a hypothesis including increased ROS (33). Angiotensin also directly affects smooth muscle function (30) and can potentiate adrenergic nerve activity and facilitate norepinephrine release (6).…”
Section: Blunting Is Improved By the Ascorbatementioning
confidence: 74%
“…In vitro data suggest that ROS can induce vasoconstriction through Rho kinase-dependent mechanisms (3). Rho kinase has been shown to have an increasingly important role in cold-induced vasoconstriction (29) and connects well with a hypothesis including increased ROS (33). Angiotensin also directly affects smooth muscle function (30) and can potentiate adrenergic nerve activity and facilitate norepinephrine release (6).…”
Section: Blunting Is Improved By the Ascorbatementioning
confidence: 74%
“…Knowledge about the mechanisms underlying the microvascular response to local cooling has greatly improved in the past few years, especially through the work by the Johnson, Kel- logg, Flavahan, and Kenney groups (18,31). Briefly, direct cooling of the skin (on the forearm) first induces an initial vasoconstriction followed by a transient vasodilation, within the first 10 -15 min after cooling onset, followed by prolonged vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, Furspan et al (13) showed increased cooling-induced ␣ 2 -adrenergic constriction of arterioles isolated from patients with primary RP compared with controls, suppressed by protein tyrosine kinase inhibitors. The role of the RhoA/Rho kinase (ROCK) pathway in mediating vasoconstriction after local cooling in healthy subjects has been confirmed in vivo (31). Indeed, cold-induced activation of ROCK may initiate constriction, mediated by both ␣ 2C -adrenoreceptors (through their mobilization from the Golgi apparatus to the vascular smooth muscle plasma membrane) and direct calcium sensitization (10).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…After the transient vasodilation a progressive sustained vasoconstriction is observed (Minson, 2010). The mechanism is complex but appears to be mediated by an adrenergic response (Thompson-Torgerson et al, 2007) in combination with decreased nitric oxide synthase (NOS) activity (Hodges et al, 2006). …”
Section: Local Coolingmentioning
confidence: 99%